The Effects of Traditional Chinese Medicine-Associated Complementary and Alternative Medicine on Women with Polycystic Ovary Syndrome. (26th February 2021) - Shen, Wenjuan; Jin, Bao; Pan, Yujia; Han, Yanhua; You, Tianjiao; Zhang, Zongyu; Qu, Yangfan; Liu, Sha; Zhang, Yang
Abstract : Polycystic ovary syndrome (PCOS) is a touchy clinical and public health problem worldwide, which adversely affects women's health and health-related comorbidities for lifetime, and represents a tremendous burden for both the family of the patient and for society. According to the diagnostic criteria used and the population studied, the prevalence rate of PCOS is between 6% and 21%. However, current conventional modern medicines for PCOS are only moderately effective at controlling the signs and symptoms, while they are not thoroughly able to prevent complications. Therefore, many patients have turned to complementary and alternative medical (CAM) treatments. CAM use is wide spread among patients with PCOS, and more than 70% of patients use CAM at one point during their diseases. The patients' primary motivations include dissatisfaction with available medications, perceive higher risk of drug side effects and crushing health burden and economic costs, desire for symptom relief, pursuit of shortening the course of disease, and the belief that CAM therapy is in accordance with the patients' values and beliefs. At present, several CAM methods have been used in women with PCOS, which has achieved obvious effects. However, biologically plausible mechanisms of the action of traditional Chinese medicine- (TCM-) associated CAM for PCOS have not been systematically reviewed. This review briefly summarizes the current progress of the impact of herbal medicine on the outcomes of PCOS and introduces the mechanisms.